Characterization of the tribological properties of bismuth-titanate coatings synthesized by sol-gel on 316L stainless steel substrates (2019)
The objective of this investigation was to obtain ceramic coatings of bismuth titanate by Sol-gel synthesis on 316L stainless steel substrates using bismuth nitrate pentahydrate (III) and titanium tetrabutoxide as precursors. The characterization focused on determining wear rates, coefficients of friction, adhesion, nano-hardness, and thickness of the coatings, depending on the concentration of the precursors, the speed of rotation and the number of layers. It is concluded that the sol presents favorable conditions for their potential application as coatings on metallic substrates